2021
DOI: 10.1007/s12311-021-01310-2
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Cerebellar Neurostimulation

Abstract: The first attempts at using electric stimulation to study human brain functions followed the experiments of Luigi Galvani and Giovanni Aldini on animal electricity during the eighteenth century. Since then, the cerebellum has been among the areas that have been studied by invasive and non-invasive forms of electrical and magnetic stimulation. During the nineteenth century, animal experiments were conducted to map the motor-related regions of cerebellar cortex by means of direct electric stimulation. As electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 218 publications
0
11
0
Order By: Relevance
“…On the other hand, computational modeling approaches could also bring additional and crucial information about lobules-specific electric field distribution in a subject-specific manner (e.g., Rezaee and Dutta, 2019 ). Such approach would allow to optimize the placement of the active electrode in order to maximize the current density through the targeted area while considering individual anatomical features ( Batsikadze et al, 2019 ; Ponce et al, 2021 ). While the present study is a purely behavioral investigation, further work using computational modeling methods would help to reduce inter-individual variability in the responsiveness to the stimulation and offer to go deeper in the mechanistic explanations related to the efficacy of the stimulation on PA and transfer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, computational modeling approaches could also bring additional and crucial information about lobules-specific electric field distribution in a subject-specific manner (e.g., Rezaee and Dutta, 2019 ). Such approach would allow to optimize the placement of the active electrode in order to maximize the current density through the targeted area while considering individual anatomical features ( Batsikadze et al, 2019 ; Ponce et al, 2021 ). While the present study is a purely behavioral investigation, further work using computational modeling methods would help to reduce inter-individual variability in the responsiveness to the stimulation and offer to go deeper in the mechanistic explanations related to the efficacy of the stimulation on PA and transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The brainstem might be inadvertently affected during cerebellar stimulation, and as such, it is recommended that studies systematically monitor physiological symptoms ( 14 , 21 ). Of the included studies, two studies examined effects on physiology (i.e., blood pressure, heart rate/pulse) in individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the current use of non-invasive neurostimulation methods to target the cerebellum, studies in the 1970-1980s used surgical methods to implant a cerebellar pacemaker in patients with schizophrenia (17)(18)(19)(20). This approach was motivated by animal research showing that the deep cerebellar nuclei are connected to the limbic system and play an important role in affective processing (21). As part of this approach, the pacemaker was implanted into the left side of a patient's chest and connected to electrodes on the cerebellar surface.…”
Section: Historical Approaches For Cerebellar Stimulationmentioning
confidence: 99%
“…These connections may explain the cerebellar involvement in disorders commonly associated with basal ganglia dysfunction, for example, Parkinson's disease. Recently, cerebellar neurons are being stimulated in human patients by brain stimulation techniques, including transcranial magnetic stimulation and transcranial direct current stimulation, to alleviate disturbances of motor control [13,[26][27][28][29]. In an animal model, Miterko reported that neuromodulation of the cerebellum rescues movement in a mouse model of ataxia [26].…”
Section: Cerebellum To Basal Gangliamentioning
confidence: 99%